Orientacje konsumpcyjne – bariera w rozwoju kapitału społecznego młodzieży akademickiej? Doniesienie z badań - Marciniak, Mateusz (Wydawnictwo Naukowe UAM, 2012)
The purpose of this paper is to analyze the relationship between the social capital and the development of the consumer society. The consumption is one of crucial contemporary analyti-cal categories. A number of social researchers claim, that we live in the consumer society. The phenomena specific to the consumer society such as commodification, consumerism or consum-erist culture are being considered as the threat to the social capital (the source of its erosion). The paper examines the relationships between consumer orientations of university students and chosen elements of their social capital: the social networks, the civic engagement and the generalized trust. The analyze is based on the findings of the research conducted in 2010’ among students of Adam Mickiewicz University (N = 446).
Consumer orientations – barrier to the development of social capital of university students? Research report
Keywords: social capital; consumerist orientations; consumerist syndrome; university students